Effect of Delivery Room Postpartum Contraceptive Implant Insertion on Initiation of Breastfeeding [11J]. (May 2020) - Shaw, Kate A.; Lerma, Klaira; Reyes, Griselda; Gutow, Hanna; Shaw, Jonathan G.
Abstract : INTRODUCTION: Initiation of postpartum contraception prior to hospital discharge has been limited by concerns about the impact of progestins on breastfeeding. Previous studies support initiation prior to hospital discharge. Insertion of the contraceptive implant in the delivery room is a convenient strategy to ensure desired contraceptive uptake prior to discharge. We designed a non-inferiority randomized controlled trial to determine if time to lactogenesis stage II (LTII; initiation of copious milk secretion) differs by timing of implant insertion. METHODS: We randomly assigned 95 pregnant people with intent to breastfeed, who desired the contraceptive implant to insertion 0-2-hours (delivery room) or 24-48-hours (delayed) post-delivery. We collected demographics and self-reported LTII using a validated tool. RESULTS: As-treated analysis included 71 participants (n=35 delivery room, n=36 delayed). Participants were similar between groups: mean age 25.5 years and median gestation over 39 weeks. The majority were admitted for labor induction (54%), used epidural anesthesia (87%) and had a vaginal delivery (81%) with no differences by group. Mean time to LTII did not differ significantly (delivery room: 64.97-hours, SD 25.1, delayed: 73.61-hours, SD 50.8; P= .37). Using an a priori margin of 12-hours, onset of LTII was non-inferior for delivery room insertion as compared to delayed insertion (mean difference -8.64-hours, 95% CI -27.69–10.42). Overall, the majority of participants achieved LTII before Day 4: 74.3% (n=26) delivery room and 72.2% (n=26) delayed, respectively ( P= .84). CONCLUSION: Postpartum insertion of the contraceptive implant in the delivery room does not delay onset of lactogenesis and should be offered.